(untitled) (Third Sector Social Economic Review, 2026)
This study evaluates the validity of the Environmental Kuznets Curve (EKC) hypothesis by examining the effects of economic growth, energy consumption, and the industrial sector on carbon dioxide emissions in Türkiye for the period 1990-2023. The main research question is whether income growth creates a non-linear relationship with environmental degradation and how the energy-industry structure shapes this relationship. In this context, annual series obtained from the World Bank WDI dataset were used; per capita CO₂ emissions were included as the dependent variable, while per capita real GDP, the square of GDP, energy consumption, and the share of industry were incorporated into the model as independent variables. Short- and long-run relationships were analyzed through the Autoregressive Distributed Lag (ARDL) bounds testing approach. The findings indicate the presence of a long-run cointegration relationship among the variables and show that the EKC hypothesis is valid for Türkiye. While income growth increases emissions, the square of income is negative and significant, confirming the inverted-U relationship. Energy consumption affects CO₂ emissions positively and strongly, whereas the effect of the industry share is not significant. The error-correction coefficient reveals a rapid adjustment of the system toward long-run equilibrium. The results suggest that environmental sustainability needs to be supported by a transition to renewable energy, energy efficiency measures, and green industrial policies, pointing to a transformation requirement aligned with Türkiye’s 2053 net-zero emission target.